Praticas insurgentes de conservação da natureza: além da institucionalização patrimonial - Silvia Helena Zanirato (Confins)
The text deals with experiences of protection of natural heritage in a small town in the Vale do Paraíba, in the state of São Paulo - Brazil, triggered by the realization of the risks of loss of this heritage, in a scenario of climate change. To this end, it discusses the logics of knowledge that are expressed in institutional and non-dialogical actions in the constitution of the heritage activated by the public power. Such actions, combined with little social participation in decision-making processes, explain conflicts around the conservation of legally protected spaces, experienced in the small city. At the same time, it addresses experiences related to climate change that motivated collective actions to protect what is considered a natural and meaningful heritage. Such actions are considered insurgent nature protection practices, triggered by a feeling of belonging and collective interest in environmental conservation